Using data from routine health information systems as a public good in Trinidad and Tobago - Marsha A. Ivey; Keisha Samlal; Alissa Moore; Donald T. Simeon (Revista Panamericana de Salud Pública)
Objective. This study aimed to explore the use of data from routine health information systems (RHIS) as a public good in Trinidad and Tobago, the challenges faced in doing this and opportunities for strengthening the health information system. Methods. For this descriptive qualitative study, purposive sampling was utilized to recruit 19 people who used or produced RHIS data. Online interviews were conducted via Zoom, and all interviews were recorded and transcribed. Pseudonyms were used to protect participants’ identity. Transcripts were cleaned and analyzed using Dedoose (v. 9.0.17; Dedoose, Los Angeles, CA, USA). Results. There was significant underutilization of RHIS data as a public good, primarily due to challenges related to data access and quality. Access to the data was stymied by burdensome bureaucratic processes, paper-based recording and storage systems, and ownership and security concerns. Data quality was adversely affected by a lack of standardized data collection forms and processes, staff training, data completeness, and also by technological and infrastructural constraints. Key opportunities for increasing the use of Trinidad and Tobago’s RHIS data would include addressing the need for a national electronic health information system, ensuring adequate training for staff involved in data management, and developing a comprehensive monitoring and evaluation plan. Conclusions. Data quality and access must be improved to enable greater use of RHIS data as a public good in Trinidad and Tobago. The planned change from a paper-based to a national electronic data recording and storage system must be expedited, and it should be accompanied by the standardization of processes, and investments in adequate staffing and timely training. Appropriate technological and infrastructural support, as well as an improved data governance system, are also required.